Proof of Stable Union for the purposes of social security benefit of pension for rural death - Feitosa , Gilliane Oliveira; Franco, Arisson Carneiro (Seven Editora, 2024)
The Federal Constitution grants State protection to stable union, and civil marriage is no longer considered valid for the definition of family, because being the base family of society, stable union, is linked to this new family form. This article aims to demonstrate proof of stable union for the purposes of social security benefit of pension for rural death, showing the necessary requirements to obtain this type of benefit. Therefore, it was necessary to have a research methodology to ensure an updated perspective on the subject, a bibliographic and exploratory excerpt addressing the historicity of stable union in the differentiation of civil marriage, seeking authors’ concepts on the subject, how it arose and what requirements were used to prove this social status, and how the right to the benefit of pension for rural death was clear. It is concluded that just as civil marriage is supported by law to guarantee a social security benefit of pension for rural death for the surviving spouse and child, people who live in a stable union are also in the same quality because it is clear that the criteria exist, as being a public, continuous and lasting union and that has the objective of family constitution. DOI:https://doi.org/10.56238/sevened2024.018-015